2013
DOI: 10.1002/cphc.201300075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Li⋅⋅⋅π Interaction on the H/X⋅⋅⋅π Interactions in HOLi⋅⋅⋅C6H6⋅⋅⋅HOX/XOH (X=F, Cl, Br, I) Complexes

Abstract: The influences of the Li···π interaction of C6H6···LiOH on the H···π interaction of C6H6···HOX (X=F, Cl, Br, I) and the X···π interaction of C6H6···XOH (X=Cl, Br, I) are investigated by means of full electronic second-order Møller-Plesset perturbation theory calculations and "quantum theory of atoms in molecules" (QTAIM) studies. The binding energies, binding distances, infrared vibrational frequencies, and electron densities at the bond critical points (BCPs) of the hydrogen bonds and halogen bonds prove that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 89 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…The applications of the Group V σ‐hole interactions in molecular recognition, crystal engineering, and biological systems are affected mainly by the strength and direction of the Group V σ‐hole interactions. The halogen bonds could display cooperative effect with other types of intermolecular interactions . Then, could the Group V σ‐hole interactions be strengthened by the addition of halogen bonds?…”
Section: Introductionmentioning
confidence: 99%
“…The applications of the Group V σ‐hole interactions in molecular recognition, crystal engineering, and biological systems are affected mainly by the strength and direction of the Group V σ‐hole interactions. The halogen bonds could display cooperative effect with other types of intermolecular interactions . Then, could the Group V σ‐hole interactions be strengthened by the addition of halogen bonds?…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the quantum theory of atoms in molecules (QTAIM) [42],which has been successfully characterize diverse kinds of noncovalent interactions [43,44], was employed to analyze the weakly bonded interactions under investigation. The topological analysis was carried out with the AIMAll program [45].The density difference in molecular formation was analyzed using Multiwfn software [46].…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Like hydrogen bonds, cooperativity and substituent effects are also present among halogen bonds. Recently, the cooperativity between halogen bond and other types of interactions has been extensively studied [34][35][36][37]. For instance, Lu et al [38] found a strong cooperativity between halogen bonds and cation-π interactions in complexes involving aromatic molecules as halogen bond donors.…”
Section: Introductionmentioning
confidence: 99%